Refractive outcomes after cataract surgery - Khoramnia, Ramin; Auffarth, Gerd U.; Łabuz, Grzegorz; Pettit, George; Suryakumar, Rajaraman (Diagnostics, 2022)
A post-operative manifest refractive error as close as possible to target is key when performing cataract surgery with intraocular lens (IOL) implantation, given that residual astigmatism and refractive errors negatively impact patients’ vision and satisfaction. This review explores refractive outcomes prior to modern biometry; advances in biometry and its impact on patients’ vision and refractive outcomes after cataract surgery; key factors that affect prediction accuracy; and residual refractive errors and the impact on visual outcomes. There are numerous pre-, intra-, and post-operative factors that can influence refractive outcomes after cataract surgery, leaving surgeons with a small “error budget” (i.e., the source and sum of all influencing factors). To mitigate these factors, precise measurement and correct application of ocular biometric data are required. With advances in optical biometry, prediction of patient post-operative refractory status has become more accurate, leading to an increased proportion of patients achieving their target refraction. Alongside improvements in biometry, advancements in microsurgical techniques, new IOL technologies, and enhancements to IOL power calculations have also positively impacted patients’ refractory status after cataract surgery.